Jesus and the Samaritan woman : a speech act reading of John 4:1-42 - Botha, J. Eugene. (Novum Testamentum, Supplements, 1991)
This book deals with two aspects pertaining to the understanding of John. On the one hand it examines the style of the Gospel and on the other hand it introduces, for the first time in the study of the Fourth Gospel, a comprehensive speech act reading of a Johannine discourse. In the first chapter different approaches to Johannine style are identified, and the deficiencies current in perceptions regarding style are indicated. The second chapter deals with theoretical observations regarding the nature of style in terms of modern stylistics. It is suggested that a possible paradigm for a comprehensive approach to style is speech act theory. The next chapter contains a comprehensive speech act reading of John 4: 1-42. Finally, observations regarding style, and understanding Johannine texts, based on this speech act reading, is given. Not only does this study clarify the nature of Johannine style in more modern terms, but it also gives an indication of the enormous possibilities this theory holds for enhancing New Testament exegesis.